PENGARUH KUALITAS PRODUK, PROMOSI DAN EVENT MARKETING TERHADAP KEPUTUSAN PEMBELIAN PERUMAHAN CEMARA PARK RESIDENCE - intan, sri; heryenzus, heryenzus (SCIENTIA JOURNAL, 2021)
This study aims to determine whether there is an influence between product quality, promotion and event marketing on purchasing decisions of Cemara Park Residence housing. Researchers conducted research with a total sample of 112 respondents based on the Slovin formula. The method of data analysis was carried out using multiple linear regression analysis. The data quality test in this study used validity and reliability tests, the assumption tests in this study were normality test, multicollinearity test, heteroscedasticity test and effect test using multiple linear regression and determination coefficient tests, while hypothesis testing in this study used t and f tests. with the help of statistical software SPSS 25. Based on the results of t-test research, it shows that the variable product quality, promotion and event marketing has a positive and significant effect on purchasing decisions, which means that Ha is accepted and Ho is rejected. The results of the f-test research indicate that product quality, promotion and marketing events together have a positive and significant effect on purchasing decisions, which means that Ho is rejected and Ha is accepted.